2019
DOI: 10.1007/s00122-019-03428-8
|View full text |Cite
|
Sign up to set email alerts
|

European maize landraces made accessible for plant breeding and genome-based studies

Abstract: Key messageDoubled-haploid libraries from landraces capture native genetic diversity for a multitude of quantitative traits and make it accessible for breeding and genome-based studies.AbstractMaize landraces comprise large allelic diversity. We created doubled-haploid (DH) libraries from three European flint maize landraces and characterized them with respect to their molecular diversity, population structure, trait means, variances, and trait correlations. In total, 899 DH lines were evaluated using high-qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 42 publications
(51 reference statements)
5
86
0
Order By: Relevance
“…This indicates that the transcriptomic variation observed in our study mainly reflects general genotypic differences and only to a minor degree differences in cold tolerance or cold treatment effects. Substantial genetic variability between genotypes in contrast to treatment effects, as observed in our experiments, was also described in previous studies on the diversity of European flint landraces accessed through doubled haploids [4,8,27]. Similar results were obtained in a set of diverse European flint and dent inbred lines subjected to heat stress where the transcriptomic responses between heat tolerant and susceptible genotypes were highly divergent [33].…”
Section: Transcriptomic Diversity With Respect To Cold Tolerancesupporting
confidence: 90%
See 2 more Smart Citations
“…This indicates that the transcriptomic variation observed in our study mainly reflects general genotypic differences and only to a minor degree differences in cold tolerance or cold treatment effects. Substantial genetic variability between genotypes in contrast to treatment effects, as observed in our experiments, was also described in previous studies on the diversity of European flint landraces accessed through doubled haploids [4,8,27]. Similar results were obtained in a set of diverse European flint and dent inbred lines subjected to heat stress where the transcriptomic responses between heat tolerant and susceptible genotypes were highly divergent [33].…”
Section: Transcriptomic Diversity With Respect To Cold Tolerancesupporting
confidence: 90%
“…We hypothesized that European maize landraces display substantial variation for cold tolerance thus carrying beneficial alleles for this trait which might not be present in elite material. This notion is supported by a study which demonstrated that in a panel of 35 European maize flint landraces including "Petkuser Ferdinand rot" used in this study, one landrace covers at least 75% of the genomic variation of all landraces present in this panel [27]. Phenotypic variation in the DH population derived from the European maize flint landrace "Petkuser Ferdinand rot" used in this study was demonstrated by > 4-fold changes in cold tolerance of root growth (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the following, we will consider genotypic data of 910 doubled haploid (DH) lines of two European maize ( Zea mays ) landraces ( n = 501 Kemater Landmais Gelb (KE) and n = 409 Petkuser Ferdinand Rot (PE), (Holker et al . 2019)) genotyped using the 600k Affymetrix® Axiom® Maize Array (Unterseer et al .…”
Section: Methodsmentioning
confidence: 99%
“…In the following, we will consider genotypic data of 910 doubled haploid (DH) lines of two European maize (Zea mays) landraces (n ¼ 501 Kemater Landmais Gelb (KE) and n ¼ 409 Petkuser Ferdinand Rot (PE), (Hölker et al 2019)) genotyped using the 600k Affymetrix Axiom Maize Array (Unterseer et al 2014). Markers were filtered for being assigned to the highest quality class (Poly High Resolution (Pirani et al 2013)), having a callrate of at least 90%, and for having at most 5% heterozygous calls, as no heterozygous calls are expected for DH lines.…”
Section: Genotype Data Usedmentioning
confidence: 99%